EVALUASI PROGRAM/PROYEK PENGEMBANGAN KAWASAN EKONOMI KHUSUS SEI MANGKE DALAM RANGKA PELAKSANAAN KEBIJAKAN MP3EI 2011-2025 DI KORIDOR EKONOMI SUMATERA - Firrean Suprapto (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
Special Economic Zones (SEZ) is a region with certain limits within the jurisdiction of Indonesia which is set to perform economic functions and obtain certain facilities. One SEZ developed in North Sumatra Province and included in the National Strategic Area (KSN) Medan - Binjai - Deli Serdang - Karo is SEZ Sei Mangke. SEZ Sei Mangke is defined in PP 29 of 2012 on 27 February 2012 and is the first KEK in Indonesia which was inaugurated its operation by President Joko Widodo on January 27, 2015. KSN Mebidangro itself is an area of ​​priority spatial arrangement because it has a very important influence nationally against state sovereignty, defense and state security, economic, social, cultural, and / or environment, including areas designated as world heritage. This research is an evaluative research intended to find out the end of a policy program in order to determine recommendation of last policy by using CIPO model which includes four stages: (1) context, (2) input, (3) process, and (4) output. The research method used is case study by applying qualitative research that aims to make an accurate interpretation of the characteristics of the object under study. Findings on the evaluation context indicate that the program is generally running well, but some aspects of synergy and policy optimization as well as financing support from central and local government need to be improved. In the input evaluation, and evaluation process some aspects need to be improved because the findings show the weakness of some aspects is the result of lack of synergy and optimization of policy and support from local government. Interesting from the evaluation of ouput is that with some weaknesses in the input and process components, it turns out the evaluation findings ouput show Seek Mangke SEZ development can still run well. The recommendation of this research is to improve the quality of policy synergy / program of SEZ Seek development by improving several aspects that are categorized in each stage of evaluation.